Inkluzivní didaktika v praxi základní školy Teorie, výzkum a praxe - Bartoňová, Miroslava (Masaryk University Press, 2020)
Title in English: Inclusive Didactics in Elementary School Practice: Theory, Research and Practice The aim of the methodological book is to depict the education of the children with partial function deficits in preschool age and to introduce the specifics of education of the pupils with specific learning difficulties and cognitive disability. The main focus is devoted to a role of the teachers in the inclusive education in terms of the concept of the intervention of the pupils with special needs. The research includes an analysis and an interpretation of the questionnaire SDQ Cze which was administered at the beginning and the end of the school year at the examined inclusive classrooms and the controlled classrooms of the participating schools.